Optimizing Communication for a Humanoid Subs-Talker Robot Using RSSI Analysis on ROS System - Burhanudin Yusuf Abdullah Ar Ramadhan; Mochammad Haidar Ridho; Anisatul Qomariyah; Siti Sendari; Yogi Dwi Mahandi (Syntax Corporation Indonesia, 2024)
This study aims to optimize communication for the humanoid